Numerical study on the effect of loading on the admittance signatures acquired in the electromechanical impedance technique - Lim, Darren Tze Yang. (2010)
Structural health monitoring (SHM) forms an integral part in maintaining the reliability and serviceability of the structures in every one’s everyday life. The application of electromechanical impedance (EMI) technique in SHM provides an indication for damage detection by reflecting changes in the stiffness of the structure. Simulation using finite element method (FEM) to apply EMI techniques helps analyst in understanding the behaviour of the structure materials and allow the analyst to determine the state of health of the structures.